Home-region focus and performance of family firms: The role of family vs non-family leaders - Banalieva, Elitsa R; Eddleston, Kimberly A (Journal of International Business Studies, 2011)
Do family firms benefit more from a regional or a global geographic scope? We suggest it depends on their family leadership type – family vs non-family leadership. We offer a nuanced view of agency and stewardship theories to hypothesize that family leaders are most beneficial when pursuing a regional strategy (i.e., high home-region focus (HRF)), whereas non-family leaders are more advantageous when pursing a global strategy (i.e., low HRF). Utilizing a sample of 202 Western European firms from 1996 to 2006, we find support for this central hypothesis. Thus family leadership influences the degree to which family firms benefit from HRF.